Exploring Trends: Five-Year Analysis of Suicide Rates in Nepal - Ganesh Bhandari; Laxman Nath; Prakash Raj Bhatt; Rima Mishra; Ashish Bhatt (Mental Illness)
Conclusion: The increasing trend in suicide rates at both the national and provincial levels highlight the necessity to prioritize this issue and it is imperative for all levels of government to formulate targeted policies, programs, and strategies to prevent suicide.